Effectiveness of written emotional disclosure interventions for eating disorders: a systematic review and meta-analysis - Wang, Yufei; Xu, Tao; Tao, Yuexian; Cai, Xintong (Frontiers in Nutrition, 2024)
Background: Eating disorders are disorders that can seriously impair the health and well-being of 9 patients. Written emotional disclosure has been recognized as a therapeutic technique that may be 10 helpful in aiding patients' emotional and psychological adjustment. However, it is unclear what 11 favorable effects eating disorder patients can derive from written emotional disclosure therapy. This 12 study aimed to review the effectiveness of written emotional disclosure in treating eating disorders 13 using a systematic review and meta-analysis. 14Objective: This study was to examine the validity of written emotional disclosure intervention for 15 eating disorders as well as to provide guidelines for the management of eating disorders in patients. 16: Researchers independently developed inclusion and exclusion criteria according to the 17 PICOS principle and systematically searched English literature databases such as PubMed, Medline, 18 Web of Science, Cochrane Library, CINAHL, EBSCO, Embase, and so on, from the time of library 19 construction to December 2023. Cochrane Risk of Bias version 2 (RoB 2) was used to evaluate 20 literature included in this review. All the literature included in this study were randomized controlled 21 trials. Accurate information was extracted and then subjected to meta-analysis with Review Manager 22 5.4 software. The credibility of the evidence of the studies was assessed using GRADEprofiler 3.6 23 software. 24 Results: The final analysis included 13 randomized controlled trials involving 1444 participants. The 25 written emotional disclosure intervention can decrease eating disorder symptom scores (SMD = -0.20, 26 95% CI [-0.34, -0.05], Z = 2.59, P = 0.01), body dissatisfaction scores (SMD = 0.37, 95% CI [0.21, 27 0.52], Z =4.59, P <0.001), and thin ideal internalization score (SMD = 0.42, 95% CI [0.22, 0.62], Z = 28 4.12, P <0.001). Anxiety scores (MD = 0.43, 95% CI [-0.77, 1.63], Z = 0.70, P = 0.48), depression 29